An??lise dos pontos ??timos de comuta????o em sistemas com FEC Adaptativo e Sistemas H??bridos com FEC e Modula????o Adaptativos - Diogo , Elvira Salvador (2021)
In digital communication systems, changes in propagation environment can affect the polarization of the electromagnetic wave, modify the wave absorption, cause undesirable scattering, fading, among other phenomena that end up modifying the amplitude and the format of the received signal. One of the ways to protect the transmissions against the degradations introduced by the channel is implement adaptive techniques of error control and modulation. These types of techniques allow to choose for each bit frame transmitted the modulation scheme that best fits the conditions of the channel at that moment and/or add bits of redundancy to the transmitted signal to guarantee higher quality of service and better performance of the systems of communication. In this dissertation, we analyzed the optimal switching points considering adaptive FEC and a hybrid technique where adaptive modulation and adaptive FEC were combined in two different network scenarios: a traditional wireless network scenario and Cognitive Radio. The determination of the optimum switching points was based on the following performance criteria: the throughput, the delay, and the power metric. We also analyzed the influence of the channel model in the determination of optimal switching points, considering a channel model with Nakagami-m fading for both network scenarios analyzed. In the presence of the cognitive radio, the access to the environment was done opportunistically using the protocol TDMA (Time Division Multiple Access).